+0

# need help

0
68
1

-4(-3x+5)-3x=3(x-4)-6

Guest Mar 6, 2017
Sort:

#1
+1808
+10

1. Multiply each term in the parenthesis by -4, 3

$$-4(-3x+5)-3x=3(x-4)-6$$

2. Calculate the product

Multiplying two negatives equals a positive: (-)*(-)=(+)

Use rules of multiplication to calculate the expression

$$-4\times (-3x)-4\times 5-3x=3x-12-6$$

3. Collect the like terms by subtracting their coefficients

Extract the negative sign from the expression

$$12x-20-3x=-3x=3x-12-6$$

4. Subtract the numbers

$$(12-3)x-20=3x-(12+6)$$

5. Move variable to the left by adding its opposite to both sides

Move constant to the right by adding its opposite to both sides

$$9x-20=3x-18$$

6. Eliminate the opposites

$$9x-3x-20+20=3x-3x-18+20$$

7. Collect the like terms by subtracting their coefficients

Keep the sign of the number with the larger absolute value and subtract the smaller absolute value from the larger

$$9x-3x=-18+20$$

8. Subtract the numbers

$$(9-3)x=+(20-18)$$

9. Divide both sides of the equation by 6

$$6x=2$$

10. Any expression divided by itself equals 1

Write the division as a fraction

$$6x\div 6=2\div 6$$

11. Reduce the fraction with 2

$$x={2\over 6}$$

$$x={1\over 3}$$

Alternative form

$$x=\approx 0.333333$$

And there goes 30 minutes of my life...

### 13 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details